Ransomware protection in IoT using software defined networking - Azka Wani; S. Revathi (Institute of Advanced Engineering and Science, 2020)
Internet of things (IoT) is the network of physical objects connected to provide various services. IoT is expanding rapidly, and is positively influencing many areas. The impact of IoT is evident in medical field, manufacturing units and livestock. The IoT is also vulnerable to many cyber threats, owing to its limited resources and battery operation. In contemporary times the security threats like DDoS, botnet malware, man in the middle, flood attacks and ransomware are affecting the smooth functioning of IoT. Ransomware has emerged as one of the biggest threat in cyber world. Ransomware is a type of malware that stops the access to files by encrypting them and decrypts the files only when a ransom is paid. The negligence towards the IoT ransomware can result in disastrous outcomes. In this paper, the growth of ransomware attacks for past few years is shown with special focus on ransomwares threatening IoT. A detection mechanism for IoT ransomware attack is presented that is designed after study of ransomware for IoT. The proposed model monitors the incoming IoT traffic through Software Defined Network (SDN) gateway. It uses policies framed in SDN controller for detection and alleviation of ransomware in IoT.